BASIC MODELLING OF ARCHITECTURE - YAHYA , NUR FAEZAH; ABDULLAH , MOHD SUFYAN; Ts. Dr. PENIEL ANG SOON ERN; OSMAN, MOHAMAD HAIRI (2024)
This book is a comprehensive guide designed for beginners exploring Autodesk Revit software in architectural modelling. It begins by explaining the Revit user interface, an essential aspect for users to familiarize themselves with the tools provided, their organization, and how to optimize efficiency. Subsequently, the book proceeds to modelling architecture, covering topics such as project creation, constructing elevation and gridlines, wall, and floor modelling, inserting doors and windows, constructing staircases, creating railings, ceilings, and roofs. Furthermore, this book guides users through inserting building components, creating sections, and generating construction documents complete with tagging, annotation, and scheduling features. At the end of this book, there are exercise questions that offer opportunities for practical application. In conclusion, this book offers hands-on learning experiences, empowering both students and beginners using Autodesk Revit Architecture to proficiently navigate Revit and produce detailed architectural models and documentation.